Mineral-based composite antibacterial film material and method for improving antibacterial performance through surface treatment of mineral-based composite antibacterial film material

By performing corona roller discharge or laser scanning ablation on the surface of mineral-based composite antibacterial membrane materials, mineral antibacterial agents are exposed, and the problem of poor antibacterial effect caused by the encapsulation of antibacterial agents in the prior art is solved, and the improvement of antibacterial performance and reduction of production costs are achieved.

CN119505332APending Publication Date: 2025-02-25CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411655127.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Among the existing mineral-based composite antibacterial membrane materials, mineral antibacterial agents cannot be directly in contact with bacteria because they are wrapped in the matrix, resulting in poor antibacterial effects. The existing technology methods to improve antibacterial performance are complex and costly.

Method used

The surface of mineral-based composite antibacterial membrane material is treated by corona roller discharge treatment or laser scanning ablation treatment, resulting in exposure of mineral antibacterial agents and improving antibacterial properties.

Benefits of technology

This method can improve antibacterial performance by more than 15%, while reducing production costs. It has a simple treatment method and is suitable for continuous online processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505332A_ABST
    Figure CN119505332A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of mineral-based composite antibacterial film materials, in particular to a mineral-based composite antibacterial film material and a method for improving antibacterial performance through surface treatment of the mineral-based composite antibacterial film material. The mineral-based composite antibacterial film material is subjected to corona roller discharge treatment or laser scanning ablation treatment; the mineral-based composite antibacterial film material comprises a polymer film and a mineral antibacterial agent dispersed in the polymer film. The surface of the mineral-based composite antibacterial film material is treated by high-energy means of corona roller discharge treatment or laser scanning ablation treatment, so that polymer molecules can be impacted, molecular chains are broken and degraded, and tiny pores are formed in the surface; the mineral antibacterial agent on the surface of the mineral-based composite antibacterial film material can be further exposed, the structure and performance of the mineral antibacterial agent cannot be damaged or changed, and compared with an untreated mineral-based composite antibacterial film material, the antibacterial performance can be improved by 15% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mineral-based composite antibacterial film materials, and in particular to a mineral-based composite antibacterial film material and a method for improving the antibacterial performance of the material through surface treatment. Background Art

[0002] Nowadays, various types of polymer composite materials with long-lasting and strong antibacterial properties are being studied and widely used. In composite materials, since polymer films generally do not have antibacterial properties, mineral antibacterial agents are often introduced to improve the overall antibacterial properties. However, due to the melt extrusion molding method of composite materials, mineral antibacterial agents are always wrapped by the matrix and cannot directly contact with bacteria to achieve effective killing, which greatly affects the antibacterial effect of composite materials. For example, antibacterial packaging film materials, antibacterial building materials, antibacterial gauze, etc., the degree of exposure of the antibacterial agent in the surface area of ​​the composite material determines the antibacterial effect. Therefore, it is an urgent need in the industry to activate the surface of the composite material to "increase efficiency and reduce costs."

[0003] At present, in the preparation process of most antibacterial composite materials, the prior art always improves the antibacterial properties of the entire composite material by modifying the components, structure or dispersion properties of the antibacterial agent in the composite material, such as Chinese patents CN116285091A, CN114507409A, CN109135232A and CN112745565A. These measures all require changing the preparation process based on the original composite material, and even need to match new production equipment in actual production, resulting in increased research and development and preparation process costs, and the cumbersome process is not conducive to promotion and application. Therefore, there is currently a lack of a simple reprocessing method that can reduce costs and increase efficiency for various types of mineral-based composite antibacterial film materials. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a mineral-based composite antibacterial film material and a method for improving the antibacterial performance of the surface treatment thereof.

[0005] The present invention discloses a mineral-based composite antibacterial film material and a method for improving antibacterial performance of the same through surface treatment. The mineral-based composite antibacterial film material is subjected to corona roller discharge treatment or laser scanning ablation treatment; the mineral-based composite antibacterial film material comprises a polymer film and a mineral antibacterial agent dispersed in the polymer film.

[0006] Furthermore, the polymer film is a plastic film.

[0007] Furthermore, the polymer film includes one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, acrylonitrile-butadiene-styrene copolymer, polyester and polylactic acid.

[0008] Furthermore, the thickness of the polymer film is 20-100 microns.

[0009] Furthermore, the power of the corona roller discharge treatment is 1-5 kW, the frequency is 5-25 kHz, and the speed of treating the mineral-based composite antibacterial film material is 0.6 m / min-60 m / min.

[0010] Furthermore, the power of the laser scanning ablation process is 3-30W, the frequency is 40kHz, and the laser scanning rate is 0.6m / min-60m / min.

[0011] Furthermore, the mineral antibacterial agent is the nano ZnO / kaolin composite antibacterial material disclosed in CN115226723B or the modified black talc antibacterial material disclosed in CN114989494B.

[0012] Furthermore, the mineral-based composite antibacterial film material is prepared by the following method: the polymer masterbatch and the mineral antibacterial agent are uniformly mixed and granulated, and then the mixture is melt-extruded or melt-extruded and cast into a film.

[0013] After the treatment by this method, the mineral antibacterial agent on the surface of the mineral-based composite antibacterial film material can be further exposed, the antibacterial performance can be further improved, and the corresponding cost can also be controlled.

[0014] The present invention utilizes corona roller discharge treatment or laser scanning ablation treatment high energy means to treat the surface of the mineral-based composite antibacterial film material, which can produce an impact on the polymer molecules, causing the molecular chains to break and degrade the surface to create tiny pores, so that the mineral antibacterial agent on the surface of the mineral-based composite antibacterial film material can be further exposed without destroying or changing the structure and performance of the mineral antibacterial agent. Compared with the untreated mineral-based composite antibacterial film material, the antibacterial performance can be improved by more than 15%.

[0015] The method of the present invention is non-contact and can be integrated in existing various types of composite material production lines formed by melt extrusion to achieve online continuous processing and reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the SEM of the surface of the mineral-based composite antibacterial membrane material prepared and treated in Example 1;

[0017] Figure 2 This is the SEM of the surface of the mineral-based composite antibacterial membrane material prepared and treated in Example 2;

[0018] Figure 3 This is the SEM of the surface of the mineral-based composite antibacterial membrane material prepared and treated in Example 3;

[0019] Figure 4This is the SEM of the surface of the mineral-based composite antibacterial membrane material prepared and treated in Example 4;

[0020] Figure 5 This is the SEM of the film prepared in Comparative Example 1;

[0021] Figure 6 This is the SEM of the surface of the mineral-based composite antibacterial membrane material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0022] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0023] The antibacterial properties of the antibacterial composite film prepared in this embodiment were tested using a coating method.

[0024] The process is as follows: the membrane materials treated in different ways are cut into squares of fixed size (2×2 cm), and then the revived E. coli is diluted to an appropriate concentration (10 -4 ), evenly apply it on the surface of the membrane material, then cover the bacterial solution with plastic wrap to prevent environmental interference, incubate in a constant temperature shaker at 36℃ for 12 hours, then rinse off the bacterial solution after the action, dilute it year-on-year and grow it again for 6 hours, and then test the absorbance change of the bacterial solution to evaluate the order of magnitude of the colonies contained in the bacterial solution, so as to evaluate the antibacterial performance.

[0025] Embodiment 1:

[0026] A method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment.

[0027] (1) Preparation of PE antibacterial composite film:

[0028] 10 kg of polyethylene masterbatch and 2 kg of mineral antibacterial agent (modified black talc antibacterial material disclosed in CN114989494B) were pre-mixed in a high-speed mixer, the mixed raw materials were pre-granulated, and then extruded at 180° C. and cast into a film;

[0029] (2) Corona activation treatment

[0030] The composite film prepared above was subjected to corona roller discharge treatment twice. The corona roller discharge treatment power was 1 kW, the frequency was 15 kHz, and the speed of the composite film was 3 m / min.

[0031] Figure 1 This is a SEM of the surface of the mineral-based composite antibacterial film material prepared in Example 1. It can be seen from the figure that the mineral antibacterial agent is exposed on the surface of the mineral-based composite antibacterial film material. And after antibacterial testing, its antibacterial rate reaches 97%.

[0032] Embodiment 2:

[0033] A method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment.

[0034] (1) Preparation of PE antibacterial composite film:

[0035] 10 kg of polyethylene masterbatch and 2 kg of mineral antibacterial agent (nano ZnO / kaolin composite antibacterial material disclosed in CN115226723B) were pre-mixed in a high-speed mixer, the mixed raw materials were pre-granulated, and then extruded at 180°C and cast into a film;

[0036] (2) Corona activation treatment

[0037] The composite film prepared above was subjected to two corona roller discharge treatments at a power of 1 kW, a frequency of 15 kHz, and a composite film moving speed of 3 m / min.

[0038] Figure 2 This is a SEM of the surface of the mineral-based composite antibacterial film material prepared according to the technical solution of this embodiment. From the figure, it can be seen that the mineral antibacterial agent is exposed on the surface of the mineral-based composite antibacterial film material. After antibacterial testing, the antibacterial rate reached 97%.

[0039] Embodiment 3:

[0040] A method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment.

[0041] (1) Preparation of PLA antibacterial composite film:

[0042] 10 kg of PLA masterbatch and 2 kg of mineral antibacterial agent (modified black talc antibacterial material disclosed in CN114989494B) were pre-mixed in a high-speed mixer, the mixed raw materials were pre-granulated, and then extruded at 140° C. and cast into a film;

[0043] (2) Laser activation treatment

[0044] The composite film prepared above was subjected to laser scanning ablation treatment twice. The power of the laser scanning ablation treatment was 10 W, the frequency was 40 kHz, and the laser scanning speed was 3 m / min.

[0045] Figure 3 This is a SEM of the surface of the mineral-based composite antibacterial film material prepared according to the technical solution of this embodiment. From the figure, it can be seen that the mineral antibacterial agent is exposed on the surface of the mineral-based composite antibacterial film material. After antibacterial testing, the antibacterial rate reached 95%.

[0046] Embodiment 4:

[0047] A method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment.

[0048] (1) Preparation of PE antibacterial composite film:

[0049] 10 kg of polyethylene masterbatch and 2 kg of mineral antibacterial agent (modified black talc antibacterial material disclosed in CN114989494B) were pre-mixed in a high-speed mixer, the mixed raw materials were pre-granulated, and then extruded at 180° C. and cast into a film;

[0050] (2) Corona activation treatment or laser activation treatment

[0051] The composite film prepared above was subjected to a corona roller discharge treatment with a power of 1 kW, a frequency of 15 kHz, and a moving speed of 3 m / min.

[0052] Figure 4 This is the SEM of the surface of the mineral-based composite antibacterial film material prepared and treated according to the technical scheme of this embodiment. It can be seen from the figure that the mineral antibacterial agent is exposed on the surface of the mineral-based composite antibacterial film material, but compared with Example 1, the number of corona roller discharge treatments is one less, and the amount of mineral antibacterial agent exposed is less than that in Example 1. After antibacterial testing, the antibacterial rate reached 79%, and the antibacterial performance was worse than that in Example 1.

[0053] Comparative Example 1:

[0054] This comparative example prepares a film material without any addition or treatment.

[0055] (1) PE film preparation:

[0056] 10 kg of polyethylene masterbatch was extruded at 180°C and cast into a film.

[0057] Figure 5 This is the SEM image of the film prepared in Comparative Example 1.

[0058] Comparative Example 2:

[0059] Preparation of mineral-based composite antibacterial membrane materials (without any treatment).

[0060] (1) Preparation of PE antibacterial composite film:

[0061] 10 kg of polyethylene masterbatch and 2 kg of mineral antibacterial agent (modified black talc antibacterial material disclosed in CN114989494B) were pre-mixed in a high-speed mixer, the uniformly mixed raw materials were pre-granulated, and then extruded at 180° C. and cast into a film.

[0062] Figure 6 This is a SEM image of the mineral-based composite antibacterial film material prepared in Comparative Example 2. It can be seen from the image that there is very little mineral antibacterial agent exposed on the surface of the mineral-based composite antibacterial film material. After antibacterial testing, the antibacterial rate reaches 70%.

[0063] For matters not mentioned above, the prior art applies.

[0064] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment, characterized in that: The mineral-based composite antibacterial film material is subjected to a corona roller discharge treatment or a laser scanning ablation treatment; the mineral-based composite antibacterial film material comprises a polymer film and a mineral antibacterial agent dispersed in the polymer film.

2. The method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment according to claim 1, characterized in that: The polymer film is a plastic film.

3. The method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment according to claim 1, characterized in that: The polymer film includes one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, acrylonitrile-butadiene-styrene copolymer, polyester and polylactic acid.

4. The method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment according to claim 1, characterized in that: The thickness of the polymer film is 20-100 microns.

5. The method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment according to claim 1, characterized in that: The power of the corona roller discharge treatment is 1-5 kW, the frequency is 5-25 kHz, and the speed of treating the mineral-based composite antibacterial film material is 0.6 m / min-60 m / min.

6. The method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment according to claim 1, characterized in that: The power of the laser scanning ablation process is 3-30W, the frequency is 40kHz, and the laser scanning rate is 0.6m / min-60m / min.

7. The method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment as claimed in claim 1, characterized in that: The mineral antibacterial agent is the nano ZnO / kaolin composite antibacterial material disclosed in CN115226723B or the modified black talc antibacterial material disclosed in CN114989494B.

8. The method for improving the antibacterial performance of a mineral-based composite antibacterial film material by surface treatment as claimed in claim 1, characterized in that: The mineral-based composite antibacterial film material is prepared by the following method: the polymer masterbatch and the mineral antibacterial agent are uniformly mixed and granulated, and then the mixture is melt-extruded or melt-extruded and cast into a film.

9. A mineral-based composite antibacterial film material obtained by the method according to claims 1-8.

Citation Information

Patent Citations

  • Antibacterial polymer composite and preparation method

    CN109135232A

  • Polypropylene graphene antibacterial composite material and preparation method thereof

    CN112745565A

  • Antibacterial agent, antibacterial PSU composite material and preparation method of antibacterial PSU composite material

    CN114507409A

  • Modified black talc antibacterial materials, their dry preparation process, and applications

    CN114989494B

  • A nano-ZnO / kaolin composite antibacterial material and its preparation method

    CN115226723B